EFEKTIFITAS PELAKSANAAN SISTEM PEMBUKTIAN TERBALIK TERHADAP PERKARA KORUPSI DALAM MEWUJUDKAN NEGARA HUKUM DI INDONESIA - Jawade Hafidz (Majalah Ilmiah Sultan Agung, 2009)
Reversal of burden proof system arranged in Code Number 31 Year 1999 jo. Code Number 20 Year 2001. In this reversal of burden proof system, defendant have to prove that its estae not a result of public prosecutor and corruption also remain to have obligation to prove its assertion. This reversal of burden proof system conducted because is difficult of verification him to corruption doing an injustice by public prosecutor if using arranged verification system in Code Number 8 Year 1981 (Code Procedure of Criminal).Keyword : Corruption and Reversal of Burden Proof System